Analysis of the Impact of Non-Tariff Measures Policy on Indonesian Frozen Shrimp Export Performance in Main Destination Markets - Nita Aprilia; Yusman Syaukat; Faroby Falatehan (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
The shrimp commodity greatly contributes to the total export value of the fisheries sub-sector in Indonesia. In 2021 Indonesia was ranked 4th as the world's largest frozen shrimp exporting country. However, the export value of this commodity still fluctuates every year, and there are still various obstacles to the NTM policy. This study aims to analyze the performance of Indonesian frozen shrimp trade in destination markets, the application of NTM policies to trade in Indonesian frozen shrimp commodities in destination markets, and the impact of NTM policies and other factors on Indonesian shrimp exports in destination markets. This study uses an inventory approach and a gravity model. The results of the study show that the performance of Indonesia's frozen shrimp export trade has a positive trend in the 2007-2021 period. The highest growth in Indonesia's frozen shrimp exports occurred in 2014, 29.59 per cent. China has the highest implementation of NTM policies in the form of SPS and TBT, with a total of 69 policies that have an impact on Indonesian shrimp exports. The results of the estimation of the impact of NTM and other influencing factors using the gravity model show that the exchange rate and population positively affect the export volume of Indonesian frozen shrimp. In contrast, the NTM policy imposed by the importing country does not significantly affect the export volume of Indonesian frozen shrimp.